2022
DOI: 10.3389/fmolb.2021.762729
|View full text |Cite
|
Sign up to set email alerts
|

Lung Adenocarcinoma Cells Promote Self-Migration and Self-Invasion by Activating Neutrophils to Upregulate Notch3 Expression of Cancer Cells

Abstract: Background: Invasion and migration of cancer cells play a key role in lung cancer progression and metastasis. Tumor-associated neutrophils (TANs) are related to poor prognosis in many types of cancer. However, the role of TANs in lung cancer is controversial. In this study, we investigated the effect of TANs on the invasion and migration of lung adenocarcinoma.Methods: Immunohistochemistry was performed to detect the density of infiltrating TANs and the expression of Notch3 in 100 lung adenocarcinoma tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The density of infiltrating TANs is negatively related to the tumor differentiation in the lung adenocarcinoma. 34 High infiltration of CD66b + TANs is obviously associated with well differentiations in gastric cancer. 18 Whether the low-level TANs in poorly differentiated tissues in this study is related to the anti-immunity and immune tolerance caused by CD163 + TAMs and FoxP3 + Tregs still needs further research to determine.…”
Section: Discussionmentioning
confidence: 98%
“…The density of infiltrating TANs is negatively related to the tumor differentiation in the lung adenocarcinoma. 34 High infiltration of CD66b + TANs is obviously associated with well differentiations in gastric cancer. 18 Whether the low-level TANs in poorly differentiated tissues in this study is related to the anti-immunity and immune tolerance caused by CD163 + TAMs and FoxP3 + Tregs still needs further research to determine.…”
Section: Discussionmentioning
confidence: 98%
“…The protein kinase C iota activates the level of Notch3 via phosphorylating the transcription factor ELF3 and subsequent occupancy of ELF3 on the Notch3 promoter in lung adenocarcinoma 42 . The Notch3 upregulation facilitates the autologous invasion and migration of lung adenocarcinoma cells 43 . The modulation of Notch3 signaling is a pivotal factor in the progression and pathogenesis of lung cancer 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that immune cells infiltrating tumors can be influenced by interactions in the tumor microenvironment to support tumor progression (Kwantwi 2023b , 2023c ; Sheng et al 2023 ; Peng et al 2021 ; Cai et al 2020 ; Kwantwi et al 2021a ; Li et al 2021 ). Notably, autophagy induction can shape immune cells to gain protumor functions leading to therapeutic resistance and tumor progression (Bustos et al 2020 ; Ishimwe et al 2020 ; Jiang et al 2019 ; Janji et al 2018 ).…”
Section: The Tumor Microenvironment Promotes Drug Resistance Through ...mentioning
confidence: 99%